ANALISIS PENGARUH KUALITAS PRODUK, HARGA, DAN CITRA MEREK TERHADAP MINAT BELI SMARTPHONE OPPO (STUDI KASUS PADA WILAYAH JAKARTA SELATAN) - Muhamad Idris (2020)
This research is a quantitative study that aims to determine the effect of product quality, price and brand image on buying interest. The population in this study were smartphone users who lived or were active in the South Jakarta area. The sample size was taken as many as 75 respondents, with non-probability sampling technique sampling with purposive sampling method. Data collection is done through the spread of google form online questionnaires. The analysis technique used is the inferential analysis method through PLS (Partial Least Square) with SmartPLS 3.2 software. The results of this study indicate that (1) Product quality has a positive and significant effect on buying interest with a path coefficient of 0.249, (2) The price of a positive and significant influence on buying interest with a path coefficient of 0.812, (3) brand image has no negative and no significant effect on buying interest with a path coefficient of -0.102. And has an R-Square value of 0.852.